Estrus Induction and Fertility Response following Ovsynch Alone and Ovsynch plus PRID Protocol in Postpartum Anestrus Surti buffaloes - Savani, HR; Khasatiya, CT; Saxena, Swati; Patel, MD (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was undertaken to find out the estrus induction and conception rate in 18 postpartum anestrus Surti buffaloes divided equally into three groups and treated with Ovsynch protocol alone and in combination with PRID, keeping one group as control. The use of Ovsynch alone and Ovsynch + PRID protocols with fixed-time artificial insemination resulted in 100% estrus induction with 66.66% and 50.00% conception rate at induced estrus, respectively, and the overall conception rate was 83.33% in both the groups. In untreated anestrus control (n=6), only four (66.66%) buffaloes exhibited spontaneous estrus within 120 days of follow-up and conceived giving the first service and overall conception rate as 75.00% and 66.66%, respectively. The mean number of services per conception did not differ significantly among the treatment and control groups. The service periods of buffaloes under both the treatment groups were significantly (p<0.05) shorter (57.00±2.81 and 61.20±3.11 days) than the control group (104.00±20.22 days). Thus, the Ovsynch and Ovsynch + PRID protocol can be successfully used to induce fertile estrus in postpartum anestrus buffaloes.